Respuesta :
Answer:
[tex]-3(x + 4) + 5x = 24\\\\-3x - 12 + 5x = 24\\\\2x - 12 = 24\\\\2x = 36\\\\x = 18[/tex]
The solution for x in this equation is 18.
Answer:
x = 18
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
Step-by-step explanation:
Step 1: Define
-3(x + 4) + 5x = 24
Step 2: Solve for x
- Distribute -3: -3x - 12 + 5x = 24
- Combine like terms: 2x - 12 = 24
- Isolate x term: 2x = 36
- Isolate x: x = 18
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -3(18 + 4) + 5(18) = 24
- Add: -3(22) + 5(18) = 24
- Multiply: -66 + 90 = 24
- Add: 24 = 24
Here we see that 24 does indeed equal 24.
∴ x = 18 is the solution to the equation.